Cardiovascular toxicity assessment of polyethylene nanoplastics on developing zebrafish embryos. (November 2021) - Sun, Mengqi; Ding, Ruiyang; Ma, Yiming; Sun, Qinglin; Ren, Xiaoke; Sun, Zhiwei; Duan, Junchao
Abstract: Environmental exposure to nanoplastics is inevitable as the application of nanoplastics in our daily life is more and more extensively. So, the adverse effects of nanoplastics on human health are also gaining greater concerns. However, the subsequent toxicological response to nanoplastics, especially on cardiovascular damage was still largely unknown. In this regard, the evaluation of cardiovascular effects of nanoplastics was performed in zebrafish embryos. The results indicated that the no observed adverse effect level (NOAEL) of nanoplastics is 50 μg/mL. The pericardial toxicity and hemodynamic changes were assessed by Albino (melanin allele) mutant zebrafish line. Severe pericardial edema was observed in zebrafish embryos after exposure to nanoplastics. At the concentration higher than NOAEL, nanoplastics significantly decreased the cardiac output (CO) and blood flow velocity. The fluorescence images manifested that the nanoplastics could inhibit the subintestinal angiogenesis of transgenic zebrafish embryos line Tg (fli-1: EGFP), which might disturb the cardiovascular formation and development. The resulting vascular endothelial dysfunction and hypercoagulable state of circulating blood further accelerated thrombosis. Reactive oxidative stress (ROS) and systemic inflammation were also found in Wild AB and Tg (mpo: GFP) zebrafish embryos, respectively. We also found many neutrophils recruiting in the tail vein where the zebrafish embryo thrombosis occurred. Our data suggested that nanoplastics could trigger the cardiovascular toxicity in zebrafish embryos, which could provide an essential clue for the safety assessment of nanoplastics. Graphical abstract: Image 1 Highlights: Nanoplastics cause pericardial edema and cardiac toxicity in zebrafish embryos. The endothelial damage and hemodynamics changes were caused by nanoplastics. Oxidative stress and systemic inflammation were critical in nanoplastics-induced embryotoxicity.